Ibadah Hybrid sebagai Ruang Spiritualitas Digital Generasi Z di Gereja Batak Karo Protestan Yogyakarta - Ari Renta Suari Br. Tarigan (Sekolah Tinggi Teologi Sriwijaya, 2026)
The development of digital technology has transformed the way people communicate, build relationships, and experience spirituality, particularly among Generation Z as digital natives. This transformation challenges the church to rethink its ministry practices, including worship practices that integrate physical and digital spaces. This study aims to analyze hybrid worship as a space for digital spirituality among Generation Z at Gereja Batak Karo Protestan (GBKP) Yogyakarta. Using a qualitative case study approach, data were collected through semi-structured interviews, observation, and documentation involving pastors, multimedia ministry teams, and Generation Z members actively participating in hybrid worship. The findings indicate that hybrid worship is not merely a technological adaptation after the COVID-19 pandemic but has become a new space for spiritual experience, community connection, and active participation in church ministry. Generation Z does not perceive digital worship as a replacement for physical worship but as an extension of faith experience that provides flexibility and maintains connection with the church community. Through dialogue with James Emery White’s perspective on Generation Z, Elizabeth Drescher’s concept of digital spirituality, and the idea of networked ministry, this study proposes the model of hybrid spirituality for Generation Z, consisting of three dimensions: authentic spiritual experience, digital spirituality, and participatory network ministry. This model emphasizes that the church in the digital era is called not only to utilize technology as a ministry tool but also to create spaces where Generation Z can encounter God, build community, and actively participate in the life and mission of the church.